UPAYA PENEMUAN DAN PENGEMBANGAN OLAHRAGA BARU â€œPANCOAIRâ€ SEBAGAI OLAHRAGA REKREASI DALAM RANGKA MENINGKATKAN DAYA TARIK WISATA AIR - SYAHRI ALHUSIN (Universitas Tunas Pembangunan, 2013)
In order to increase innovative and creative work as a lecturer, I try to create a real work that is hoped able to give positive benefit in the development. As a lecturer of entrepreneurship subject for the students of Health and Education of Teacher Training and Education Faculty of UTP, so I try to engineer a kind of new sport that I name â€œPanco Airâ€. Inspiration of â€œPanco Airâ€ came from smashing game that I had done since I was in grade 5 together with my friends in my age. The play site was on a pathway bridge over a river 5 meter wide and 1,2 meters deep located in Srikaton village, Tugumulyo subdistrict, Musi Rawas Regency, South Sumatra. Since I have been teaching in Teacher Training and Education Faculty, Health and Sport Education UTP, I invite my fellow sport lecturers to discuss smashing game to become a sport. Besides that, because since 1996, I have taught entrepreneurship subject, so I make a creation to invent â€œPanco Airâ€ Sport. And I make it to become a lecture material. Through some discussions with my fellow lecturers and students, I succeded to find â€œPanco Airâ€ game in the year 2000. In 2001 we got Uberhaki Program for making patent for â€œPanco Airâ€ support device. In 2002 we got MURI Award number 802/R.MURI/X/2002 as the firstinisiator of â€œPanco Airâ€ Sport in Indonesia. In 2002 we got program Student Alternative Work from General Directorate of High Education with Project Number 37/P4M/DPPM/WUB/IV/2002. Through Students Alternative Program we have done socialitation for â€œPanco Airâ€ Sport in some swimming pools in Regencies surrounding Surakarta ( Manahan Solo, Kopassus Kartasura, Pengging Boyolali, Jambeyan Klaten and Jati Diri Sport Arena Semarang). On March 2003, we presented â€œPanco Airâ€ Sport in an International Seminar, that was â€œInternational Conference on Sport Sciences and Physical Education Profession, Development in Facing Global Challenges, in Indonesian University of Education, Bandungâ€. In 2010, we made a unit of â€œPanco Airâ€ Sport support with a little improvement. For the next, finding and development of â€œPanco Airâ€ has always become parts of lecture materials, for semester six students. In the entrepreneurship lecture in 2012, that was followed by 300 students from 5 classes, it had been done seminar and exhibition of â€œPanco Airâ€ Sport as well, where all students were asked to give feedback to study and develop â€œPanco Airâ€ Sport.